Itinerari di ricerca intorno a Vico e a Leopardi: potenza e limitatezza dell'umana conoscenza - Manuela Sanna (I Quaderni del LAB, 2017)
Research paths around Vico and Leopardi: power and limits of human knowledge. This volume collects the papers presented at a seminar held in Potenza in November 2016 and constitutes the first outcome of a research project promoted by the Istituto per la storia del pensiero filosofico e scientifico moderno of the National Research Council, the Centro nazionale di studi leopardiani in Recanati, together with the National Library Vittorio Emanuele III in Naples and a network of Italian and foreign universities. The aim is to reflect on the relationship between Vico and Leopardi by reading jointly the Scienza nuova and the Zibaldone, without neglecting traces spread in other works, as well as the identification of the sources inside Vico's and Leopardi's libraries. The research bears witness to the fortune of the Scienza nuova in the early XIXth century and shows how Vico and Leopardi recapture in their works issues debated throughout Europe. Among them the relationship between philosophy and poetry, the analysis of the forms of knowledge (i.e., "poetical wisdom", "fairy tale", "myth"), the semantics of imagination, the relationship between civilization and barbarism, as well as language-related issues such as "origins of languages", "symbolic language", "language and thought".